Photobiomodulation- Current concept and its application in dentistry - D.R, Mahesh; Pandeshwar, Padma; David, Chaya M; G, Komali; D, Dinesh; vernekar, Sayi kavitha T (International Journal of Dental Research, 2013)
Light therapies are widely used in various clinical therapeutics which includes photodynamic therapy to kill cancer cells; UVA therapies used to treat a variety of skin diseases and Photobiomodulation used for promoting cell growth and recovery from injury using light emitting diodes or low energy lasers, From a clinical perspective, PBM offers dental practitioners a non-invasive and non-thermal treatment modality that can be used as an adjunct to traditional therapies or as a therapeutic tool on its own as patient’s acceptance of PBM is incredibly high, in this review we present to you the mechanism of action and clinical applications of Photobiomodulation in various fields of dentistry.